Caracterização numérica e experimental de estruturas CSRR em antenas de microfita - Álef Huan Pereira Souto; Jefferson Costa e Silva; Marília Gabriella Alves Rodrigues Santos; Alfredo Gomes Neto (Revista Principia, 2019)
This work aims to perform the numerical and experimental characterization of CSRR (Complementary Split Ring Resonator) structures in the ground plane of microstrip antennas, for the use in 4G/LTE wireless systems in the 2.5 GHz band. Two geometries for the radiating elements of the antennas were used, the circular and the rectangular ones. Some initial equations were used to design the CSRR structures, followed by a numerical optimization process. This way, numerical and experimental analyzes of the changes in antennas characteristics were carried out, mainly in resonance frequency, bandwidth and radiation pattern. The simulated results were obtained using the commercial software ANSYS, which uses the Moment Method (MoM). The simulated and measured results of the antennas with the CSRR structures printed on their ground plane were compared with those obtained by circular and rectangular patch antennas with a conventional ground plane, we could observe a reduction in their resonant frequency, enabling the miniaturization process.